Atualização da rede hidrográfica digital da bacia hidrográfica do rio Teles Pires como subsídio para o monitoramento hídrico e sistema de regularização ambiental - Barros, Ana Paula Santos (2022)
The management of water resources is an activity that is necessary and urgent nowadays, requiring resources that allow environmental agencies to control and monitor these resources more accurately and quickly. Remote sensing is a tool that has allowed these results to be achieved in a more comprehensive way over large areas. Therefore, the objective of this work was to update the hydrographic network of the Teles Pires river basin to serve as a subsidy for the environmental monitoring of the hydrographies of the state of Mato Grosso as well as to generate data that contributes to the environmental regularization system. To achieve the goal, the automatic extraction of new drainage from the digital elevation model, analysis and validation by satellite images in the ArcGIS software was performed, which generated the delimitation and validation of a greater number of hydrographs, using the visual analysis by satellite image of the new drainage, being possible the manual vectorization of 6,068.1 km of new hydrographs, adding the on-site visit of six selected points, where only in one point there was no trace of hydrography. However, it can be concluded that further detailing of the entire area studied will be necessary, whether by satellite image vectoring or field visits, since it is a large region, but it is safe to say that the product achieved in this work can serve as geographic data for activities that require the geolocation of a large number of hydrographs of the Teles Pires river basin